VD_FINDINFO HC / 2009 / 420 vom 5. Oktober 2009 - VD Tribunal cantonal (2009)
COURTAGE, COMMERCE D'IMMEUBLES, COURTIER, INTERROGATOIRE, TÉMOIN | 412 CO, 413 CO, 414 CO, 339 al. 2 CPC, 339a al. 3 CPC, 452 al. 1 CPC, 452 al. 2 CPC, 456a CPC, 470 al. 1 CPC